Pengaruh Orientasi Gaya Kepemimpinan Terhadap Disiplin Kerja Pegawai di Badan Kepegawaian Daerah Kota Bandung - Sugina, Gina; Suryana, Asep; Prihatin, Eka (UPI, 2016)
This study entitled âThe Influence of Leadership Style to EmployeeâsÂ Discipline in Bandung Staffing Berau (Badan Kepegawaian Daerah (BKD)Â Kota Bandung)â. The research questions of this study is about employeeâsÂ discipline who work in Bandung Staffing Berau.Â The aims of this study is obtain the actual picture of the influence of theÂ orientation of leadership style on employeeâs discipline in BKD KotaÂ Bandung. The method used in this research is descriptive method with aÂ quantitative approach. While the data collection techniques used through thequestionnaire enclosed with a four rating scale (Likert). Population is used asÂ a source of data in this research study as well as the sample is the entireemployee BKD Kota Bandung by 94 employees.Â Based on the results of data processing computed by using the WMS (WeightÂ Means Scored) showed that the average general tendency for the variable X (Orientation Leadership Style) of 3.13 and be in the good category, and theÂ general trend of the average for the variable Y (Employeeâs Discipline ) ofÂ 3.21 to be in good category. Results of testing normality of data distribution,Â it is known that the variables X and Y variables are normally distributed.Â Judging from the calculation of the correlation coefficient of 0.625 whichÂ shows that there is a strong relationship between variables X and variable Y,Â while the calculation of significant test of 7.680 proved significant. TheÂ results of the analysis of the determination coefficient of 39.06% shows theÂ influence of the influence of leadership style to employeeâs discipline is atÂ 39.06% and the rest of them are influenced by other factors. The regressionÂ equation Ì means each one unit increase of leadershipstyle variable provides the increase of employeeâs discipline as much as 0.625Â unit. This study conclusion states leadership style effects significantly toemployeeâs discipline in BKD Kota Bandung.